Investigation of Biomarkers Associated with Osteoporosis Among Women Patients: Penelitian Biomarker yang Terkait dengan Osteoporosis pada Pasien Wanita - Al- anbaki; Ali Abdulameer (Academia Open, 2026)
Background: Biochemical indicators and endocrine factors, particularly thyroid hormones and sex hormones, are closely related to bone metabolism and skeletal regulation in women. Knowledge Gap: Although several biomarkers are known to participate in bone metabolism, the combined profile of biochemical and hormonal parameters associated with osteoporosis in women remains insufficiently documented in certain regional populations. Aims: This study investigated selected biochemical and hormonal biomarkers in women diagnosed with osteoporosis in Al-Diwaniyah Governorate. Results: A total of 76 women aged 25–45 years participated in the study and were divided into an osteoporosis group (46 patients) and a healthy control group (30 individuals). Statistical analysis showed significant reductions in body mass index, serum calcium, and vitamin D levels in osteoporotic women compared with controls. In contrast, thyroid-related hormones, including thyroid-stimulating hormone and thyroxine, were significantly elevated in the patient group. Additionally, estrogen and follicle-stimulating hormone concentrations were significantly lower in women with osteoporosis. Novelty: The study provides an integrated evaluation of biochemical and endocrine biomarkers related to bone metabolism among women within the studied population. Implications: These findings highlight the importance of hormonal and biochemical assessment in understanding metabolic alterations associated with osteoporosis and may support clinical laboratory monitoring strategies for women at risk of bone metabolism disorders. Keywords: Osteoporosis, Bone Metabolism, Thyroid Hormones, Vitamin D, Women Key Findings Highlights Reduced calcium, vitamin D, and body mass index detected in affected participants. Elevated thyroid-related hormones identified in the patient group. Lower estrogen and follicle-stimulating hormone concentrations observed in osteoporotic women.